Enhanced flow sensing with interfacial microstructures. Issue 1 (25th February 2020) - Jiang, Yonggang; Zhao, Peng; Ma, Zhiqiang; Shen, Dawei; Liu, Gongchao; Zhang, Deyuan
Abstract : Biological flow receptors show astonishing performance and are used as models for the design of novel flow sensors. However, the functional importance of interfacial microstructures is seldom discussed in previous review papers. Herein, this review summarises the underlying biomechanical principles in the biological flow receptors and describes the recent progress in bio‐inspired flow sensors, in which the underlying sensing‐enhancement mechanisms are emphasised.